Strategic Curriculum Design for Brand Building: An Analysis of the Islamic Fashion Institute's Curriculum as a Strategic Communication Tool in Constructing Institutional Brand Identity and Brand Equity - Hanni Haerani; Dede L Chaerowati (Interdisciplinary Social Studies, 2026)
This research aims to analyze how a fashion design training curriculum based on Muslim dress principles serves as a strategic communication tool to build institutional brand identity and brand equity at the Islamic Fashion Institute (IFI), Bandung, Indonesia. The study employs a qualitative approach with an intrinsic case study method. Data were collected through triangulation, including in-depth interviews with curriculum designers and instructors, document analysis of the syllabi, and focus group discussions (FGD) with alumni and active students. Thematic analysis was applied using Kapferer’s Brand Identity Prism and Keller’s Customer-Based Brand Equity (CBBE) framework. The results indicate that the Sharia-based curriculum acts as the core brand message and a meaning-making system. The integration of Fiqh (Islamic Jurisprudence) of fashion, Islamic aesthetics, and Sharia business ethics serves as a potent brand differentiator. This "substance-led" branding constructs a robust "Culture" dimension, creating an authentic brand experience that elevates institutional brand equity through high brand resonance among graduates. Research limitations/implications As a single-site case study focusing on a pioneer vocational institution, the findings may have limited generalizability to conventional fashion schools. Future research could explore the application of this curriculum-based branding model in different cultural or religious educational contexts. Practical implications For Islamic educational institutions, the study suggests that branding should be rooted in pedagogical substance rather than mere external promotion. Developing a unique, values-driven curriculum can serve as a sustainable competitive advantage in the global Halal industry. Originality/value This research proposes a novel conceptual framework: Curriculum-Based Branding. It shifts the paradigm from marketing-led communication to an internal-out approach where the curriculum itself functions as the primary strategic communication instrument to construct institutional identity.